Răspuns :
a(b+c)=520
a×52=520
a=520:52=10
a(b-c)=45
a×9=45
a=45:9=5
a(b+c)+70=170
25(b+c)=170-70
b+c=100:25=4
a(b-c)-48=2
10(b-c)=2+48
b-c=50:10=5
a×52=520
a=520:52=10
a(b-c)=45
a×9=45
a=45:9=5
a(b+c)+70=170
25(b+c)=170-70
b+c=100:25=4
a(b-c)-48=2
10(b-c)=2+48
b-c=50:10=5
ab+ac =520
b+c =52
a×b+a×c = a×(b+c)=520
a×52=520
a= 520:52
a= 10
ab-ac = 45
b-c = 9
ab- bc = a×( b-c) =45
a×9 =45
a= 45:9
a= 5
b+c =52
a×b+a×c = a×(b+c)=520
a×52=520
a= 520:52
a= 10
ab-ac = 45
b-c = 9
ab- bc = a×( b-c) =45
a×9 =45
a= 45:9
a= 5